Molecular basis for cellular retinoic acid-binding protein 1 in modulating CaMKII activation - Nhieu, Jennifer; Miller, Michelle C.; Lerdall, Thomas A.; Mayo, Kevin H.; Wei, Li-Na (Frontiers in Molecular Biosciences, 2023)
Introduction: Cellular retinoic acid (RA)-binding protein 1 (CRABP1) is a highly conserved protein comprised of an anti-parallel, beta-barrel, and a helix-turn-helix segment outside this barrel. Functionally, CRABP1 is thought to bind and sequester cytosolic RA. Recently, CRABP1 has been established as a major mediator of rapid, non-genomic activity of RA in the cytosol, referred to as “non-canonical” activity. Previously, we have reported that CRABP1 interacts with and dampens the activation of calcium-calmodulin (Ca2+-CaM)-dependent kinase 2 (CaMKII), a major effector of Ca2+ signaling. Through biophysical, molecular, and cellular assays, we, herein, elucidate the molecular and structural mechanisms underlying the action of CRABP1 in dampening CaMKII activation. Results: We identify an interaction surface on CRABP1 for CaMKII binding, located on the beta-sheet surface of the barrel, and an allosteric region within the helix segment outside the barrel, where both are important for interacting with CaMKII. Molecular studies reveal that CRABP1 preferentially associates with the inactive form of CaMKII, thereby dampening CaMKII activation. Alanine mutagenesis of residues implicated in the CaMKII interaction results in either a loss of this preference or a shift of CRABP1 from associating with the inactive CaMKII to associating with the active CaMKII, which corresponds to changes in CRABP1’s effect in modulating CaMKII activation. Conclusions: This is the first study to elucidate the molecular and structural basis for CRABP1’s function in modulating CaMKII activation. These results further shed insights into CRABP1’s functional involvement in multiple signaling pathways, as well as its extremely high sequence conservation across species and over evolution.